2019
DOI: 10.1371/journal.pone.0219637
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific changes in size and shape of the ligaments and tendons of the porcine knee during post-natal growth

Abstract: Prior studies have analyzed growth of musculoskeletal tissues between species or across body segments; however, little research has assessed the differences in similar tissues within a single joint. Here we studied changes in the length and cross-sectional area of four ligaments and tendons, (anterior cruciate ligament, patellar tendon, medial collateral ligament, lateral collateral ligament) in the tibiofemoral joint of female Yorkshire pigs through high-field magnetic resonance imaging throughout growth. Tis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The length of the vector between the centroids of the tissue‐specific tibial insertion and the femoral ACL insertion was calculated using a custom code for each tissue (Figure 2). CSA was calculated as described in a previous paper 23,24 . Briefly, each the tissue model was imported into Matlab, rotated such that the longest tissue axis matched the z‐ axis of a coordinate system, and then the surface was collapsed onto x ‐ y planes at 1 mm increments along the z ‐axis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of the vector between the centroids of the tissue‐specific tibial insertion and the femoral ACL insertion was calculated using a custom code for each tissue (Figure 2). CSA was calculated as described in a previous paper 23,24 . Briefly, each the tissue model was imported into Matlab, rotated such that the longest tissue axis matched the z‐ axis of a coordinate system, and then the surface was collapsed onto x ‐ y planes at 1 mm increments along the z ‐axis.…”
Section: Methodsmentioning
confidence: 99%
“…CSA was calculated as described in a previous paper. 23,24 Briefly, each the tissue model was imported into Matlab, rotated such that the longest tissue axis matched the z-axis of a coordinate system, and then the surface was collapsed onto x-y planes at 1 mm increments along the z-axis. The CSA was then calculated as the average of the areas measured within these 2D features in the central 50% of the tissue.…”
Section: Geometric Measurementsmentioning
confidence: 99%
“…The rodent ACL is positioned within the knee in comparable anatomical location to humans, but the hierarchical organization of the ACL is less complex in rodents, especially mice, compared to humans 9 . However, several studies, 5,10–13 including our recent work, 14–16 have shown that the ACL still serves as a primary restraint to tibial anterior translation (Figure 2). Therefore, these anatomical limitations do not change the primary function of the ligament or the ability of rodent models to answer key mechanistic and biology questions.…”
Section: The Aclmentioning
confidence: 96%
“…Longitudinal studies with fluorescent reporters and in vivo whole animal imagers are also an option for rodent studies but remain uncommon in large animal studies. Moreover, noninvasive imaging techniques, such as magnetic resonance imaging or ultrasound [3][4][5][6] can be done using similar sequences and at similar resolution in large animal models as used for humans, 7,8 and joint kinematics are more commonly done in large animal species. In small animal models, longitudinal imaging of bone and the enthesis via micro computed tomography and soft tissues with high resolution 7−10 T MRI and/or 50−55 MHz ultrasonography are also possible but the resolution can be limited by the small size of the rodent tendon and ligament.…”
Section: Whatmentioning
confidence: 99%
“…4,18 Pigs from 1.5 to 3 months of age have greater translation and rotation in the stifle joint as compared to adolescents (4.5-18 months). 38 In pigs, the anterior cruciate ligament is the primary stabilizer of the stifle, and its anatomy changes substantially during early development, gaining substance and changing orientation, affecting joint kinematics, 38,39 and it is likely that the same is true in foals less than 6 months of age. 18 Equine stifle joint kinematics at any age is challenging to investigate, and available information is limited to an unloaded ex vivo study of femur and tibias from adult horses.…”
Section: Scl Etiologymentioning
confidence: 99%